Building Students Motivation In Writing Skill for Islamic Education - Tb. Endayani M.Pd (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2017)
This paper is written to examine how to build learners motivation in writing for Islamic education students. everybody knows how to write is the most draining and thinking but that is for the unmotivated person to be with the motivated. motivation is itself a person's impulse to do something that arises because of his/her own desires and the encouragement of others. a teacher plays a major role in motivating learners to continue writing by giving them writing assignments, in addition to giving rewards also included. for learners to defeat the opponent is the greatest motivation to show its advantages. As for the writing phase starts from copying to developing the natural idea of a paragraph. if the learners are not motivated or less motivated in writing, it will be very difficult in developing the idea.